Overground gait kinematics and muscle activation patterns in the Yucatan mini pig. (1st April 2022) - Mirkiani, Soroush; Roszko, David A; O'Sullivan, Carly L; Faridi, Pouria; Hu, David S; Fang, Daniel; Everaert, Dirk G; Toossi, Amirali; Konrad, Peter E; Robinson, Kevin; Mushahwar, Vivian K
Abstract: Objective. The objectives of this study were to assess gait biomechanics and the effect of overground walking speed on gait parameters, kinematics, and electromyographic (EMG) activity in the hindlimb muscles of Yucatan minipigs (YMPs). Approach. Nine neurologically-intact, adult YMPs were trained to walk overground in a straight line. Whole-body kinematics and EMG activity of hindlimb muscles were recorded and analyzed at six different speed ranges (0.4–0.59, 0.6–0.79, 0.8–0.99, 1.0–1.19, 1.2–1.39, and 1.4–1.6 m s −1 ). A MATLAB program was developed to detect strides and gait events automatically from motion-captured data. The kinematics and EMG activity were analyzed for each stride based on the detected events. Main results. Significant decreases in stride duration, stance and swing times and an increase in stride length were observed with increasing speed. A transition in gait pattern occurred at the 1.0 m s −1 walking speed. Significant increases in the range of motion of the knee and ankle joints were observed at higher speeds. Also, the points of minimum and maximum joint angles occurred earlier in the gait cycle as the walking speed increased. The onset of EMG activity in the biceps femoris muscle occurred significantly earlier in the gait cycle with increasing speed. Significance. YMPs are becoming frequently used as large animal models for preclinical testing and translation of novel interventions to humans. A comprehensive characterization of overground walking in neurologically-intact YMPs is provided in this study. These normative measures set the basis against which the effects of future interventions on locomotor capacity in YMPs can be compared.